2006
DOI: 10.3171/spi.2006.4.1.20
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of unexpected and important histopathological findings in routine intervertebral disc surgery

Abstract: Object The value of routine histopathological examination of intervertebral disc tissue has been questioned, but sufficient numbers of studies have yet to be conducted to provide a definitive sense of its importance. The aim of this study was to investigate the nature and frequency of unexpected histopathological findings in intervertebral disc surgery. Methods The authors conducted a retrospective exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Those diagnoses were not benign and consisted of amyloidosis with unusual immunological features, metastatic prostate carcinoma, and diffuse large B-cell lymphoma 16,17 . While the rate of discordant diagnoses found within the intervertebral disc space during routine surgical intervention approximated that seen with total hip and knee arthroplasty and shoulder and knee arthroscopy, more malignant diagnoses were observed.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Those diagnoses were not benign and consisted of amyloidosis with unusual immunological features, metastatic prostate carcinoma, and diffuse large B-cell lymphoma 16,17 . While the rate of discordant diagnoses found within the intervertebral disc space during routine surgical intervention approximated that seen with total hip and knee arthroplasty and shoulder and knee arthroscopy, more malignant diagnoses were observed.…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have demonstrated extremely low diagnostic value and high costs of histological examinations following a variety of procedures, including thumb, knee, and hip arthroplasty; lumbar and cervical discectomy; hallux valgus surgery; wrist ganglion excision; and shoulder and knee arthroscopy [6][7][8][9][10][11][12][13][14][15][16][17][18][19][23][24][25][26][27][28] (see Appendix). While these represent various procedures under different settings, different clinical and histological diagnoses occurred in 0% to 9% of the cases.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations